Joining thick section aluminum to steel with suppressed FeAl intermetallic formation via friction stir dovetailing. (15th April 2018) - Reza-E-Rabby, Md.; Ross, Kenneth; Overman, Nicole R.; Olszta, Matthew J.; McDonnell, Martin; Whalen, Scott A.
Abstract: A new solid-phase technique called friction stir dovetailing (FSD) has been developed for joining thick section aluminum to steel. In FSD, mechanical interlocks are formed at the aluminum-steel interface and are reinforced by metallurgical bonds where intermetallic growth has been uniquely suppressed. Lap shear testing shows superior strength and extension at failure compared to friction stir approaches where metallurgical bonding is the only joining mechanism. High resolution microscopy revealed the presence of a 40–70 nm interlayer having a composition of 76.4 at.% Al, 18.4 at.% Fe, and 5.2 at.% Si, suggestive of limited FeAl3 intermetallic formation. Graphical abstract: Unlabelled Image